2003
DOI: 10.1021/ja028800s
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chalcogenolate Complexes as Capping Agents in the Synthesis of Ternary II−II‘−VI Nanoclusters:  Structure and Photophysical Properties of [(N,N-tmeda)5Zn5Cd11Se13(SePh)6(thf)2]

Abstract: We report the synthesis of the complex (N,N'-tmeda)Zn(SeSiMe3)2 (1), whose pendant trimethylsilyl moieties result in a powerful reagent for the generation of ternary MM'E materials. Reaction of 1 with (PnPr3)2Cd(OAc)2 and PhSeSiMe3 has led to the formation of the ternary ZnCdSe nanocluster [(N,N-tmeda)5Zn5Cd11Se13(SePh)6(thf)2] (2). The cluster consists of a CdSe core capped by ZnSe2 units, and represents the first example of a structurally characterized II-II'-VI nanocluster. Utilization of an analogous (trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Kanatzidis et al studied the suitability of mixed copper indium chalcogenolates as precursor materials for the photovoltaic materials CuInE 2 (E = S, Se). [1,10] Corrigan et al observed room-temperature fluorescence for the ternary 12-12Ј-16 cluster (12 = Zn; 12Ј = Cd; 16 = Se), [(N,N,NЈ,NЈ-tmeda) 5 Zn 5 Cd 11 Se 13 (SePh) 6 (THF) 2 ], [9] while binary cadmium or zinc selenide clusters showed weak luminescence only at temperatures below 50 K. During recent studies, it was found that the investigation of these compounds containing complex mixtures of elements needs a combination of various investigative approaches to reach conclusions with confidence. [4] We report herein the synthesis, structural characterization, and theoretical investigation of [As(C 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanatzidis et al studied the suitability of mixed copper indium chalcogenolates as precursor materials for the photovoltaic materials CuInE 2 (E = S, Se). [1,10] Corrigan et al observed room-temperature fluorescence for the ternary 12-12Ј-16 cluster (12 = Zn; 12Ј = Cd; 16 = Se), [(N,N,NЈ,NЈ-tmeda) 5 Zn 5 Cd 11 Se 13 (SePh) 6 (THF) 2 ], [9] while binary cadmium or zinc selenide clusters showed weak luminescence only at temperatures below 50 K. During recent studies, it was found that the investigation of these compounds containing complex mixtures of elements needs a combination of various investigative approaches to reach conclusions with confidence. [4] We report herein the synthesis, structural characterization, and theoretical investigation of [As(C 6 …”
Section: Introductionmentioning
confidence: 99%
“…Examples for different classes of compounds include [Cu 6 In 3 (SEt) 16 ](PPh 4 ), [1] [M I 6 M III 8 Cl 4 E 13 (PPh 3 ) 6 ] (M I = Cu, Ag; M III = Ga, In; E = S, Se), [2] [Cu 11 In 15 Se 16 (SePh) 24 (PPh 3 ) 4 ], [3] [Ag 26 In 18 S 36 -Cl 6 (dppm) 10 (THF) 4 ][InCl 4 (THF)] 2 , [4] [Hg 15 Cu 20 S 25 (PnPr 3 ) 18 ], [5,6] [Cu 4 Nb 2 Se 6 (PMe 3 ) 8 ], [7] [Ta 4 Cu 12 Cl 8 S 12 (PMe 3 ) 12 ] [8] and [(N,N,NЈ,NЈ-tmeda) 5 Zn 5 Cd 11 Se 13 (SePh) 6 (THF) 2 ]. [9] Interest in these compounds arises for several reasons: (a) investigation of the structural build-up of a certain composition of elements with respect to existing and nonexisting bulk phases, (b) development of precursor compounds for the production of thin films of ternary materials and (c) investigation of the properties of nano-sized species. With respect to (a), it was found that most of the cluster structures formed by elements of group 11-13-16 20 ] -remained ambiguous with respect to the assignment of one of the copper atoms, we performed a high-resolution mass spectrometric analysis as well as DFT computations to address this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of different compounds include (PPh 4 )[Cu 6 In 3 (SEt) 16 ], [1] 6 ] (M I = Cu, Ag; M III = Ga, In; E = S, Se), [2] [Cu 11 In 15 Se 16 -(SePh) 24 (PPh 3 ) 4 ], [3] [Ag 26 In 18 S 36 Cl 6 (dppm) 10 (thf) 4 ][InCl 4 -(thf)] 2 , [4] [Hg 15 Cu 20 S 25 (PnPr 3 ) 18 ], [5,6] [Cu 4 Nb 2 Se 6 (PMe 3 ) 8 ], [7] [Ta 4 Cu 12 Cl 8 S 12 (PMe 3 ) 12 ], [8] [(N,NЈ-tmeda) 5 Zn 5 Cd 11 Se 13 -(SePh) 6 (thf) 2 ], [9] and [(py) 8 Ln 4 M 2 Se 6 (SePh) 4 ] (Ln = Er, Yb, Lu; M = Cd, Hg). [10] Interest in these compounds lies in the characterization of their structures and an investigation of their properties.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the manipulation of their surfaces via ligand selection/design has become an important focus in this arena of chemistry. The incorporation of specific ligands onto nanoclusters has been found to have marked effects on the optical and electronic properties of these materials (DeGroot et al 2003).…”
Section: Surface Functionalization Of Metal Chalcogenide Nanoclustersmentioning
confidence: 99%
“…Bis(trimethylsilyl)chalcogenides, E(SiMe 3 ) 2 , are prepared via the addition of chlorotrimethylsilane, ClSiMe 3 , to an alkali metal chalcogenide, M 2 E (M = Na, Li) (So & Boudjouk 1989), generated from either the reduction of elemental chalcogen with sodium metal in aqueous ammonia or ethereal solvents (So & Boudjouk 1989;DeGroot et al 2003), or with lithium triethylborohydride (Thompson & Boudjouk 1988;So & Boudjouk 1989).…”
Section: Preparation Of Silylated Reagentsmentioning
confidence: 99%